1987
DOI: 10.1021/bi00384a012
|View full text |Cite
|
Sign up to set email alerts
|

Selective isolation of human plasma low-density lipoprotein particles containing apolipoproteins B and E by use of a monoclonal antibody to apolipoprotein B

Abstract: A monoclonal antibody to human plasma apolipoprotein B was used in a single-step immunoaffinity chromatography procedure to isolate a subpopulation of low-density lipoprotein particles from normolipidemic human plasma. The isolated particles were homogeneous in terms of size (20 nm), flotation coefficient (Sf = 9.5), and electrophoretic mobility (beta band). Their protein moiety consisted of apolipoproteins B and E in a molar ratio close to 2. The lipid moiety consisted of 47.3% cholesterol, 4.7% triglycerides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…In contrast, the relative atherogenic capacities of Lp-B:C:E and Lp-B:E particles may be less pronounced than that of Lp-B particles. This might be due to high rates of the lipolytic degradation of Lp-B:C:E particles on one hand [49] and high affinity binding and uptake of Lp-B:E particles by LDL receptors on the other [50]. Under normal metabolic conditions, plasma levels of Lp-B:C:E and Lp-B:E particles are relatively low except in hypercholesterolemic and hypertriglyceridemic states [63].…”
Section: Results Of Clas and Mars Trials Have Demonstrated That Some mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the relative atherogenic capacities of Lp-B:C:E and Lp-B:E particles may be less pronounced than that of Lp-B particles. This might be due to high rates of the lipolytic degradation of Lp-B:C:E particles on one hand [49] and high affinity binding and uptake of Lp-B:E particles by LDL receptors on the other [50]. Under normal metabolic conditions, plasma levels of Lp-B:C:E and Lp-B:E particles are relatively low except in hypercholesterolemic and hypertriglyceridemic states [63].…”
Section: Results Of Clas and Mars Trials Have Demonstrated That Some mentioning
confidence: 99%
“…Furthermore, it has been demonstrated that the three major TG-rich lipoprotein families have different affinities for lipoprotein lipase (LPL) despite almost identical TG and apoC-III contents; thus, the Lp-B:C:E particles have been found to be the most efficient substrate for LPL followed by decreasing efficiency of Lp-B:C and low efficiency of Lp-A-II:B:C:D:E particles [49]. The Lp-B:E particles bind to LDL receptors on human fibroblasts, HepG2 and HeLa cells with greater affinity than Lp-B particles [50,51]; in contrast, the binding of Lp-B:C and Lp-B:C:E particles with phenotype E2/E2 to LDL receptors of HeLa cells has been found to be negligible, suggesting that these lipoprotein families have very little effect on the regulation of HMG-CoA reductase activity [51]. All these findings provide strong evidence for the crucial role of minor apolipoproteins in modifying and determining the metabolic properties of individual apoA-and apoB-containing lipoproteins.…”
Section: Lipoprotein Family Conceptmentioning
confidence: 99%
“…The protein moiety is actually thought to have an important role in the formation of epitopes. In this way, Koren et al 39 have described a Cl MAb that is specific for a particular conformation of apo B expressed in lipoprotein particles containing apo B and apo E exclusively as protein components. Finally, in a recent in vivo metabolic study performed with various LDL density subpopulations from subjects with normolipidemia and familial combined hyperlipidemia, it has been suggested that the presence of non-apo B apolipoproteins could influence the metabolic behavior of different LDL subclasses.…”
Section: Discussionmentioning
confidence: 99%
“…96 Sequential immunoaffinity chromatography or immunoprecipitation has revealed the existence of 3 major species of plasma lipoproteins containing both apoE and apoB 97 : LpB:C:E particles (ie, TRL containing apoC-I, C-II, C-III, and apoE); LpA-II:B:C:D:E particles (ie, TRL containing several apolipoproteins including apoA-II and apoE, characteristic of patients with Tangier disease or type V hyperlipoproteinemia 98 ); and LpB:E particles (ie, cholesteryl ester-enriched lipoproteins resembling LDL with apoE. 99 Two additional apoB-containing lipoproteins in human plasma are LpB:C particles (ie, TRL containing only C apolipoproteins) and LpB (ie, LDL containing only apoB 100 ). It remains to be determined which of these lipoprotein species best represents TRL remnants.…”
Section: Quantification Of Remnant Lipoproteins According To Apolipopmentioning
confidence: 99%